4-Quinolone N-Oxides as Bacterial Weapons - Szamosvári, D.; Böttcher, T. (Synlett, 2018)
Various bacterial species are known to produce metabolites of the 4-quinolone N-oxide class. These compounds have antibiotic activities, and are believed to target the respiration of competing microbes by interfering with menaquinone-binding sites in enzymes of the electron-transport chain. Interestingly, even minor structural changes in related N-oxides produced by the same organism can produce a dramatic difference in antibiotic activity, suggesting possible functional specialization.
Keywords: Pseudomonas; Burkholderia; respiratory chain; metabolites; cytochromes; antibiotics